Mechanical properties of NiTi and CuNiTi wires used in orthodontic treatment. Part 2: Microscopic surface appraisal and metallurgical characteristics - Marco Abdo Gravina; Cristiane Canavarro; Carlos Nelson Elias; Maria das Graças Afonso Miranda Chaves; Ione Helena Vieira Portella Brunharo; Cátia Cardoso Abdo Quintão (Dental Press Editora, 2014)
OBJECTIVE: This research aimed at comparing the qualitative chemical compositions and the surface morphology of fracture regions of eight types of Nickel (Ni) Titanium (Ti) conventional wires, superelastic and heat-activated (GAC, TP, Ormco, Masel, Morelli and Unitek), to the wires with addition of copper (CuNiTi 27oC and 35oC, Ormco) after traction test. METHODS: The analyses were performed in a scanning electronic microscope (JEOL, model JSM-5800 LV) with EDS system of microanalysis (energy dispersive spectroscopy). RESULTS : The results showed that NiTi wires presented Ni and Ti as the main elements of the alloy with minimum differences in their composition. The CuNiTi wires, however, presented Ni and Ti with a significant percentage of copper (Cu). As for surface morphology, the wires that presented the lowest wire-surface roughness were the superelastic ones by Masel and Morelli, while those that presented the greatest wire-surface roughness were the CuNiTi 27oC and 35oC ones by Ormco, due to presence of microcavity formed as a result of pulling out some particles, possibly of NiTi. 4 The fracture surfaces presented characteristics of ductile fracture, with presence of microcavities. The superelastic wires by GAC and the CuNiTi 27oC and the heat-activated ones by Unitek presented the smallest microcavities and the lowest wire-surface roughness with regard to fracture, while the CuNiTi 35oC wires presented inadequate wire-surface roughness in the fracture region. CONCLUSION: CuNiTi 35oC wires did not present better morphologic characteristics in comparison to the other wires with regard to surfaces and fracture region.